2019
DOI: 10.1088/1674-4926/40/1/012804
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial growth of thickα-Ga2O3film on sapphire (0001) by MIST-CVD technique

Abstract: The 8 μm thick single-crystalline α-Ga2O3 epilayers have been heteroepitaxially grown on sapphire (0001) substrates via mist chemical vapor deposition technique. High resolution X-ray diffraction measurements show that the full-widths-at-half-maximum (FWHM) of rocking curves for the (0006) and (10-14) planes are 0.024° and 0.24°, and the corresponding densities of screw and edge dislocations are 2.24 × 106 and 1.63 × 109 cm−2, respectively, indicative of high single crystallinity. The out-of-plane and in-plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 28 publications
(43 reference statements)
2
35
2
1
Order By: Relevance
“…Thus, more attention is urgently required to improve the quality of α-Ga 2 O 3 now and in the future. Recently, highly crystalline α-Ga 2 O 3 thin films have been successfully grown at atmospheric pressure by mist-CVD on c-sapphire substrates, whose temperatures of 400–500 °C are reasonably low and the optimal growth conditions of solution concentration, growth temperature, carrier gas velocity, and film thickness have also been investigated [12,13]. However, there is still no systematical study about how the different carrier gas affects the film quality.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, more attention is urgently required to improve the quality of α-Ga 2 O 3 now and in the future. Recently, highly crystalline α-Ga 2 O 3 thin films have been successfully grown at atmospheric pressure by mist-CVD on c-sapphire substrates, whose temperatures of 400–500 °C are reasonably low and the optimal growth conditions of solution concentration, growth temperature, carrier gas velocity, and film thickness have also been investigated [12,13]. However, there is still no systematical study about how the different carrier gas affects the film quality.…”
Section: Introductionmentioning
confidence: 99%
“…1(d). Within each individual domain, the atomic steps are straight and elongated along the [11][12][13][14][15][16][17][18][19][20] and no surface depressions within the terraces are observed. Existing theories developed for dislocation mediated surface morphologies have been employed to interpret the formation of pinned steps, spiral growth hillocks, and surface depression.…”
mentioning
confidence: 99%
“…The detailed growth conditions have been described elsewhere. 17 By increasing the growth time, a series of a-Ga 2 O 3 films were achieved with their nominal thickness ranging from 80 nm to 8 lm as determined from optical reflection spectra recorded using a UV-visible spectrometer (Lambda 950, PerkinElmer). It was reported that cracks were often formed on the surface of thick a-Ga 2 O 3 films (>3 lm) without any buffer layer, which result from the accumulated thermal stress induced by the thermal expansion mismatch between a-Ga 2 O 3 and sapphire.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated band gaps of α‐, β‐, and κ‐Ga 2 O 3 are consistent with experiments and earlier theoretical reports. [ 14,48–50 ] The wide band gaps are particularly important for next‐generation semiconducting devices operating at much higher temperatures.…”
Section: Resultsmentioning
confidence: 99%